#TITLE_ALTERNATIVE# - ANGGA KUSUMA (NIM 12103022), NIZAR
Indonesia is a country with unstable geological condition. That conditions make the pipeline installation in Indonesia become unsafe due to the dangerous geological activities or called geohazards. For example like earthquake, landslide, ground movement etc which all are extremely dangerous for the pipeline operation. In this research, the type of geohazard that will be studied is fault which is divided into three types, there are strike-slip fault, normal fault, and reverse fault. Another variable that also will be studied is the material type of pipe there are X-42, X-52, X-65, and X-80 pipe material related to the API 5L spesification of line pipe. Later, the pipe-soil interaction will be modeled using a software based on finite element analysis. During simulation, the force will be applied to the pipe through the soil deformation. The output value derived from the simulation are stress, plastic strain and pipe's cross-section deformation. Analysis show that the value of stress, strain, and pipe's cross-section deformation are increasing equal with the increasing value of soil deformation. It also shows that the highest value of stress, strain, and pipe's cross-section deformation are derived from the reverse fault case, followed later by normal and strike-slip fault. For example in X-65 pipe grade at 1,25 m of soil deformation where the stress and plastic strain value for the reverse, normal, and strike-slip fault are 506 MPa, 501 MPa, 486 MPa, and 0,08 ; 0,06 ; 0,03 respectively. Later the safety factor analysis show that the increasing of pipe grade will affect to the increasing value of pipe sustainability related to the soil deformation. For example in strike-slip fault case where the pipe undergo the plastic deformation after 0,625m ; 0,57 m ; 0,5 m ; 0,45 m of soil deformation for X-80, X-65, X-52, and X-42 pipe grade respectively.